Failure of Glass Fibre-Reinforced Polypropylene Metal Laminate Subjected to Close-Range Explosion - Bassiri Nia, Amin; Xin, Li; Yahya, Mohd Yazid; Ayob, Amran; Farokhi Nejad, Ali; Rahimian Koloor, Seyed Saeid; Petrů, Michal (Polymers, 2020)
The present study investigates the effects of close-range blast loading of fibre metal laminates (FMLs) fabricated from woven glass polypropylene and aluminium alloy 2024-T3. The polypropylene layers and anodized aluminium are stacked in 3/2 layering configuration to investigate the impact energy absorbed through deformation and damage. In order to study the blast responses of FMLs, a 4-cable instrumented pendulum blast set-up is used. Effects of blast impulse and stand-off distance were examined. Investigation of the cross-section of FMLs are presented and damages such as fibre fracture, debonding, and global deformation are examined. Increasing stand-off distance from 4 to 14 mm resulted in a change of damage mode from highly localized perforation to global deformation.
Keywords: hybrid structure; blast; failure mode and deformation; composite; impulse